Оцінка працездатності парку тракторів у системі технічного сервісу АПК у «АГРОСПЕЦЕКСПОРТ» м. Кропивницький - Тарасенко, Євген Олегович; Tarasenko, Yevhen (ЦНТУ, 2024)
Метою даної роботи є розробка методології формування якості функціонування системи технічного сервісу парку тракторів АПК шляхом обґрунтування складу системи обслуговування. Під системою спеціалізованого технічного обслуговування АПК ми розуміємо сукупність служб технічного обслуговування сільськогосподарських підприємств і дилерів, що містять штат виконавців технічного сервісу або сервісних інженерів, які мають необхідні технічні засоби для здійснення сервісної діяльності. Проведений аналіз ефективності виробничої діяльності ТОВ «АГРОСПЕЦСЕРВІС» та обґрунтовано тему магістерської роботи її актуальність та задачі дослідження. Описані технології технічного обслуговування і ремонту та проведений аналіз математичної моделі формування якості технічного обслуговування та ступенів відповідності елементів якості технічного сервісу. Розроблено систему технічного сервісу при встановлених цілях діяльності, а саме відомого складу тракторного парку та відомих технологій і виконавців ТО і ремонту. Описана реалізація технічного сервісу тракторів господарства мобільними ланками, що показала високу ефективність роботи групи виконавців. The purpose of this work is to develop a methodology for the formation of the quality of the functioning of the technical service system of the tractor fleet of the agricultural industry by substantiating the composition of the service system. Under the system of specialized technical maintenance of the agricultural industry, we understand the totality of technical maintenance services of agricultural enterprises and dealers, which include a staff of technical service performers or service engineers who have the necessary technical means to carry out service activities. The analysis of the efficiency of the production activity of "AGROSPETSSERVIS" LLC was conducted and the topic of the master's thesis was substantiated, its relevance and research objectives. Technical maintenance and repair technologies are described, and the analysis of the mathematical model of the formation of the quality of maintenance and the degree of conformity of elements of the quality of technical service is carried out. A system of technical service has been developed with the established goals of the activity, namely the known composition of the tractor fleet and known technologies and performers of maintenance and repair. The implementation of the technical service of farm tractors by mobile units is described, which showed the high efficiency of the work of the group of performers.
Evaluation of the tractor fleet in the system of technical service of the agricultural industry in "AGROSPETSEXPORT" in Kropyvnytskyi
Keywords: працездатність; тракторний парк; технічний сервіс; агропромисловий комплекс; efficiency; tractor park; agro-industrial complex